2022
DOI: 10.3390/curroncol29110669
|View full text |Cite
|
Sign up to set email alerts
|

#COVID19 and #Breastcancer: A Qualitative Analysis of Tweets

Abstract: Rapid and efficient communication regarding quickly evolving medical information was paramount for healthcare providers and patients throughout the COVID-19 pandemic. Over the last several years, social media platforms such as Twitter have emerged as important tools for health promotion, virtual learning among healthcare providers, and patient support. We conducted a qualitative thematic content analysis on tweets using the hashtags #BreastSurgery, #BreastCancer, #BreastOncology, #Pandemic, and #COVID19. Advoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A. T. collected an additional 368 Tweets via Tweet‐Chasing between 20 July and 2 August 2021. The final sample was 415 Tweets, comparable to the amount used in similar studies 8,30–32 …”
Section: Methodsmentioning
confidence: 99%
“…A. T. collected an additional 368 Tweets via Tweet‐Chasing between 20 July and 2 August 2021. The final sample was 415 Tweets, comparable to the amount used in similar studies 8,30–32 …”
Section: Methodsmentioning
confidence: 99%
“…We used qualitative content analysis to analyze tweets from 20 maternal health advocacy organizations on Twitter. We used qualitative content analysis instead of textual machine-learning analysis because the focus was not on emotional, sentimental analysis, or word count but on categorizing, interpreting, and analyzing themes generated from the data and their meanings [34]. The traditional qualitative content analysis allowed us to detect quotes and attributions suitable to support the themes.…”
Section: Methodsmentioning
confidence: 99%
“…Naganathan et al [ 10 ] performed a qualitative analysis of tweets related to breast cancer and COVID19. Their findings from the samplsize of 403 tweets showed that advocacy organizations tweeted the most about the topic and a majority of the tweets came from the USA.…”
Section: Related Literaturementioning
confidence: 99%